Molecular characterization and vegetative growth of pathogenic seed-borne fungus, Curvularia lunata of tomato and its in vitro control measures - Billah, MB; Sikder, MM; Mallik, MRI; Hossain, MK; Alam, N (International Journal of Agricultural Research, Innovation and Technology, 2022)
Present studies were conducted to isolate and identify the seed-borne pathogenic fungus from the selected tomato variety through morphological and molecular techniques based on the sequencing of internal transcribed spacer (ITS) region of 18S rDNA. According to the colony and conidial features, the fungus was identified as Curvularia sp. The obtained ITS sequencing showed above 99% similarity with Curvularia lunata in the NCBI database. The sequence of the fungus was deposited in NCBI GenBank under the accession number: ITS, MH382879.1. Besides, the phylogenetic tree further confirmed the taxonomic position of the studied fungus. Growth characteristics of the fungus on nine different fungal culture media were evaluated, in which Honey peptone agar, Carrot agar, Potato sucrose agar, and Kauffman’s agar were found the most suitable. The maximum vegetative growth of the fungus was recorded at 30°C temperature and pH conditions. The bio-control potential of five different antagonists against the studied fungus was assessed, in which Trichoderma harzianum showed the better performance to restrict mycelial growth. Three ethanolic plant extracts were also evaluated, in which Lowsonia inermis L. exhibited above 60% mycelial growth inhibition of the fungus. Among three tested fungicides, Tilt 250 EC was found as an excellent fungicide to inhibit mycelial growth of C. lunata under in vitro conditions. Int. J. Agril. Res. Innov. Tech. 11(2): 124-132, Dec 2021